UPHOLDING THE ERGA OMNES PRINCIPLE: THE ROLE OF CONSTITUTIONAL COURT DECISIONS IN THE FORMATION OF INDONESIA'S NEW PENAL CODE: MENEGUHKAN PRINSIP ERGA OMNES: PERAN PUTUSAN MAHKAMAH KONSTITUSI DALAM PEMBENTUKAN KUHP BARU INDONESIA - Ali, Chaidir; Meidiantama, Refi (Constitutional Law Society, 2025)
The erga omnes principle, denoting obligations owed universally rather than to specific parties, plays a crucial role in constitutional law and judicial review. In Indonesia, the Constitutional Court upholds this principle by ensuring its rulings have a binding effect on all legal actors and institutions. This paper examines how the Court's jurisprudence has shaped the new Indonesian Penal Code through landmark constitutional decisions. By analyzing key rulings that annulled provisions from the colonial-era Penal Code, this study explores the Court’s influence on legislative reform and human rights protections. Utilizing normative legal research methods, including statute, case, and conceptual approaches, this study assesses how the Constitutional Court enforces the erga omnes principle through judicial review. The findings reveal that while several unconstitutional provisions from the old Penal Code were removed, some were reintroduced in the new code with modifications, often as complaint-based offenses to balance legal certainty with free expression. Despite these revisions, concerns persist regarding the potential misuse of reintroduced provisions to suppress dissent. This study underscores the Constitutional Court’s role in safeguarding democracy by ensuring its decisions are universally applicable. However, challenges remain in enforcing compliance with its rulings. As Indonesia continues its legal evolution, ongoing judicial oversight will be essential to uphold constitutional supremacy, human rights, and the rule of law.